Effect of Power Cycling and Heat Aging on Reliability and IMC Growth of Sn-5Sb and Sn-10Sb Solder Joints. (9th May 2018) - Kobayashi, Tatsuya; Shohji, Ikuo; Nakata, Yusuke
Abstract : Power cycle reliability of solder joints with Sn-5Sb (mass%) and Sn-10Sb (mass%) alloys was investigated. The effects of power cycling and heat aging on the growth of intermetallic compound (IMC) layers at the interfaces between Sn-Sb alloys and Cu plates were also investigated. In the power cycling test, the solder joint with Sn-10Sb has high reliability compared with that of Sn-5Sb. IMC layers grew in both joints with increasing number of power cycles. Compared with Sn-5Sb and Sn-10Sb, difference in growth kinetics of IMC layers was negligible. A similar tendency was observed in the heat aging test. Compared with the power cycling and the heat aging, growth of IMC layers at the aging temperature of 200°C is faster than that in the power cycling test at the temperature range of 100°C to 200°C, while that at the aging temperature of 100°C, the growth is slower. On the basis of the comparison between the power cycling and the heat aging, it was clarified that growth kinetics of IMC layers in the power cycling can be predicted by investigating growth kinetics of the IMC layer at the temperatures in the vicinity of the peak temperature in power cycling.